2020
DOI: 10.1039/c9an01588d
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopy of developing bone mineral: from amorphous precursor to mature crystal

Abstract: The developing bone mineral is comprised by an amorphous component prior to apatite crystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 68 publications
2
32
0
Order By: Relevance
“…The FTIR spectrum of the MHEM precipitate (Fig. 2 ) contains two groups of peaks corresponding to orthophosphates and carbonates similar to well-known FTIR spectra of carbonated hydroxyapatites (CHA) 24 30 . The only difference is a smoother shape of phosphate bands in MHEM as compared with standard CHA.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The FTIR spectrum of the MHEM precipitate (Fig. 2 ) contains two groups of peaks corresponding to orthophosphates and carbonates similar to well-known FTIR spectra of carbonated hydroxyapatites (CHA) 24 30 . The only difference is a smoother shape of phosphate bands in MHEM as compared with standard CHA.…”
Section: Resultssupporting
confidence: 55%
“…The only difference is a smoother shape of phosphate bands in MHEM as compared with standard CHA. This difference might possibly originate from the short time interval between MHEM precipitation and its analysis and, as a consequence, amorphous structure of CHA due to its immaturity 30 .
Figure 2 FTIR spectra of control samples of commercial hydroxyapatite (HA), synthetic carbonated hydroxyapatite (CHA), and test sample of precipitated particles of MHEM from cat faeces (MB diet).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two examples of major advances in vibrational spectroscopy are the coupling of spectrometers to imaging systems and fiber optic probes, which enables an important expansion of the biomedical application of these methods. When coupled to imaging systems [ 1 , 2 , 27 , 31 , 34 , 42 , 46 , 49 , 59 , 60 , 61 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], it is possible to obtain hyperspectral images of tissue sections, in which each micron-sized pixel corresponds to a spatially-defined spectrum. Each hyperspectral image can be comprised of arrays of hundreds to thousands of spectra and allow the analysis of multiple individual components based on the selection of specific intensities or absorbances present in the spectra, presenting an excellent source of information on the amount and distribution of tissue components.…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…This study showcased a unique strength of FTIR spectroscopy for the identification of a specific absorbance band associated to an amorphous calcium phosphate mineral. By investigating a variety of developing bones, Querido et al [ 78 ] identified the existence of a transient amorphous mineral precursor formed in bone prior to apatite crystallization, which advances our knowledge of bone mineralization and development. It is also important to highlight a recent study by Imbert et al [ 74 ] where bone tissue composition and structure were assessed by AFM-FTIR spectral imaging.…”
Section: Application Of Vibrational Spectroscopy For Connective Timentioning
confidence: 99%